2011
DOI: 10.21836/pem20110503
|View full text |Cite
|
Sign up to set email alerts
|

Influence of laxatives on electrolyte and water balance in normal horses

Abstract: Beim Kolikpferd stellt der Einsatz von Laxantien den wesentlichen Teil der konservativen Behandlung primärer Obstipationen des Zäkums und großen Kolons dar. Dabei soll das über eine Nasenschlundsonde eingegebene Flüssigkeitsvolumen möglichst vollständig im Intestinaltrakt verbleiben, um die Ingesta zu durchfeuchten und so die Obstipation zu lösen. Je nach Art und Konzentration des gewählten Laxans werden Resorptions-und Sekretionsvorgänge an der Darmschleimhaut ausgelöst, die sich als Elektrolytverschiebungen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 6 publications
1
4
0
3
Order By: Relevance
“…These findings match the data of previous studies, where the bioavailability of sulphate from sodium sulphate was higher and more stable in comparison to sulphate from a magnesium sulphate, but there was no statistically significant difference (Cocchetto andLevy 1981, Morris andLevy 1983b). The fact that magnesium sulphate might cause pronounced diarrhoea (Morris and Levy 1983b) while sodium sulphate had much milder effects on bowel function (Cocchetto and Levy 1981) could not be confirmed in horses (Spallek et al 2011). When isotonic solutions of sodium or magnesium sulphate were orally administered in our study, we observed that only a very low amount was recovered in the blood, suggesting that very little of the compound was absorbed and the main part (99 %) would have to be eliminated with the faeces.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…These findings match the data of previous studies, where the bioavailability of sulphate from sodium sulphate was higher and more stable in comparison to sulphate from a magnesium sulphate, but there was no statistically significant difference (Cocchetto andLevy 1981, Morris andLevy 1983b). The fact that magnesium sulphate might cause pronounced diarrhoea (Morris and Levy 1983b) while sodium sulphate had much milder effects on bowel function (Cocchetto and Levy 1981) could not be confirmed in horses (Spallek et al 2011). When isotonic solutions of sodium or magnesium sulphate were orally administered in our study, we observed that only a very low amount was recovered in the blood, suggesting that very little of the compound was absorbed and the main part (99 %) would have to be eliminated with the faeces.…”
Section: Discussionsupporting
confidence: 85%
“…The minimal and maximal value of serum sulphate concentration in healthy fasted horses was 0.29 and 0.42 mmol/l. Results of the electrolyte and water balance have been published recently elsewhere (Spallek et al 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Urinary specific gravity is affected by the concentration of the solutes in the urine. Decreased concentrations of UUN, U-Cr, K, Ca and Cl in group 2 caused a urine specific gravity less than 1.035 (control group), however, MZ does not cause polyuria, but the horses with colic treated with laxatives could have more water intake after resolving the impaction (Spallek et al 2011). Therefore, group 2 showed significantly decreased urinary FENa, which is probably a renal compensatory mechanism.…”
Section: Variablesmentioning
confidence: 89%
“…Therefore, group 2 showed significantly decreased urinary FENa, which is probably a renal compensatory mechanism. The FECl and FEK were significantly decreased in group 2, which could be influenced by the laxative treatment with sodium sulphate (1.8 %) (Spallek et al 2011). The loop of Henle controls urine concentration via a countercurrent multiplication mechanism, which depends mainly on concentrations of urea and sodium salts in the renal medullary interstitial fluids (Sadowski andDobrowolski 2003, Schott 2010).…”
Section: Variablesmentioning
confidence: 99%